Electromagnetic interference risk from electrostatic discharge in infant incubators - Trivida, Elvina; Sudrajat, Muhammad Imam; Ardiatna, Wuwus; Prananto, Haryo Dwi; Nugroho, Hutomo Wahyu; Yoppy, Yoppy; Anam, Mohamad Khoirul; Bakti, Aditia Nur; Mandaris, Dwi; Arjadi, R Harry (Institute of Advanced Engineering and Science, 2025)
This paper proposes an improved electromagnetic compatibility (EMC) risk analysis approach for medical equipment related to the effect of electrostatic discharge (ESD). This approach not only focuses on the risk of ESD from the susceptibility aspect but also investigates its conducted electromagnetic interference (EMI) characteristics. This study combines the standardized ESD test and conducted emission (CE) measurement simultaneously, applying it to the infant incubator and analyzing the spectrum of ESD current in the phase line in the time and frequency domain. The result shows that an ESD exposure caused current spikes with an average level of 13.8 A. Moreover, it also causes a broad spectral CE noise on the phase line of the infant incubator. Furthermore, the CE noise in the low-frequency range was also detected on the phase line during ESD exposure, indicating the risk of interference with other sensitive medical equipment connected to the same power network. The approach of proposed risk analysis in this study can be used to identify the risks of EMI due to ESD events in implementing the latest IEC 60601-1-2.